Археологічні дослідження на території передмістя Переяслава Руського в 2008 р. - Тетеря, Д.А. (Археологічні дослідження в Україні, 2009)
The article presents the materials of rescue archaeology research conducted on the territory of outskirts of Pereyaslav Ruthenian in 2008. New data on the history of shaping of this part of the mediaeval city was obtained, and one of the Ancient Rus trading centres of bone processing was localised.